From grains to tracks: high-resolution sedimentology of track-bearing Stormberg strata, southern Africa - Mpangala, Loyce Elesia (Department of Geological Sciences, 2024)
Tracks registration is influenced by the dynamic interplay between the pedal anatomy of the trackmaker, its behaviour, and the substrate conditions it interacts with. Differences in substrate conditions, especially those linked to grain size and moisture content, often result in the most dramatic variations in track morphology. In the upper Stormberg Group, main Karoo Basin of southern Africa, diverse trace fossils, primarily comprising Upper Triassic– Lower Jurassic dinosaur tracks, are preserved. Extensive studies have been carried out to document these individual tracksites and to examine the variations between sites and through time, with recent studies suggesting that track abundance and anatomical fidelity increase up-stratigraphy. Despite the well-established understanding of the effects of substrate on track registration and preservation, these past studies have not specifically focused on the substrate conditions, and when substrate conditions were considered, the emphasis was primarily on macro-sedimentary features. Here, we examine the microsedimentary features of track-bearing units in the upper Stormberg Group using petrographic techniques, to better understand the palaeosubstrate and its effect on fossil track registration and preservation. The analysis revealed that very fine-grained sands and substrates modified by microbial activity tend to preserve tracks with greater abundance and higher anatomical fidelity. Furthermore, the prevalence of very fine-grained and microbially modified strata, and their associated track trends, increases in younger stratigraphic units. Across the Triassic– Jurassic boundary of southern Africa, there was a proliferation of dinosaur populations, possibly linked to the end–Triassic mass extinction events, which has been credited globally for track abundance increases in the Lower Jurassic. However, our findings suggest that, locally, the observed increase in track abundance (and anatomical fidelity) up-stratigraphy may also be linked to substrate–composition differences, which were ultimately controlled by large-scale changes in the palaeoenvironment from high-energy meandering fluvial to lowerenergy aeolian-lacustrine settings in the Late Triassic and Early Jurassic, respectively